2021
DOI: 10.3390/agronomy11030510
|View full text |Cite
|
Sign up to set email alerts
|

Wood Vinegar as a Complex Growth Regulator Promotes the Growth, Yield, and Quality of Rapeseed

Abstract: Wood vinegar is formed by the condensation of smoke produced during the production of biochar. It mainly contains acetic acid, butyric acid, catechol, and phenol. Wood vinegar has a compound effect of promoting crop growth similar to plant growth regulators and is environmentally friendly. Moreover, it can enhance the biological and abiotic resistance of crops. In this study, foliar spraying was carried out systematically in the field with the hybrid variety of Huayouza 9 for two years to study the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 35 publications
8
40
0
1
Order By: Relevance
“…However, the effect of PA in our study conducted under greenhouse conditions revealed a different result. Other studies [ 15 ] reported results similar to our experiments, showing little difference between control and PA-treated rapeseed plants over different development stages (seedling, bud bolting, and flowering) except for at the pod stage (182 days after sowing). Interactive effects between chemical fertilizer and biochar application on SPAD were observed in our study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, the effect of PA in our study conducted under greenhouse conditions revealed a different result. Other studies [ 15 ] reported results similar to our experiments, showing little difference between control and PA-treated rapeseed plants over different development stages (seedling, bud bolting, and flowering) except for at the pod stage (182 days after sowing). Interactive effects between chemical fertilizer and biochar application on SPAD were observed in our study.…”
Section: Resultssupporting
confidence: 90%
“…Additional benefits of PA for agriculture include promotion of plant growth [ 1 ] and soil health [ 13 , 14 ]. Application of PA has been observed to increase seed germination and root growth [ 15 ], perhaps the result of organic acids converting unavailable soil P into phosphoric acid for nutrient uptake [ 16 ]. According to Wang et al [ 17 ], several plant-growth promoting mechanisms may be triggered in parallel by PA application: (1) accumulation of proteins involved in different pathways of secondary metabolism, stress response, and carbohydrate metabolism; (2) accumulation of antioxidant enzymes, and (3) decreased reactive oxygen species (ROS) and malonaldehydes in root tissue [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…PA is commonly used as a biostimulant to improve plant growth and productivity [6]. Depending on the concentration, PA can be used as an antimicrobial agent [19,20], a herbicide [21], a soil enhancer [22], and an insect repellent [23] or promote root development [24,25] and microbial activities [26] when diluted. Recent studies reported that PA enhances seed germination rate, vegetative and reproductive growth of several plants species [6,24,25,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolytic bio-derivates, extracted from wood plants, bamboo, herbaceous plants, and algae are largely used in the agriculture practices [1]. The different features of wood distillates converge in a consolidated strengthening power in agricultural production [2]. In fact, in spite of the biomass from which they are extracted and the subsequent processing methods, an increase in agricultural production and plant resistance to biotic and abiotic stress, which adversely affect agricultural production or product quality, is reported.…”
Section: Introductionmentioning
confidence: 99%